Architectural, energy and information engineering : proceedings of the 2015 international conference on architectural, energy and information engineering (AEIE 2015), Xiamen, China, May 19-20, 2015 /: proceedings of the 2015 international conference on architectural, energy and information engineering (AEIE 2015), Xiamen, China, May 19-20, 2015. (2015) - Unknown
No abstract available